Evaluating Liquid Influence on Low-Cost Piezoelectric Transducer Response for Elastic Emission Machining Monitoring † - Lopes, Thiago Glissoi [UNESP]; Freire, Leonardo Darri [UNESP]; da Cunha, Pedro Augusto [UNESP]; Aguiar, Paulo Roberto [UNESP]; França, Thiago Valle [UNESP] (MDPI, 2022)
Elastic emission machining (EEM) is a finishing process for the surface of parts. In the EEM of ceramic parts, the part is submerged into a liquid interface that contains abrasive particles, and then a spindle rotates a spheric tool rapidly, forcing the abrasive particles into contact with the ceramic surface part. Due to the fact that it is a finishing process, the part that goes through EEM has a high aggregated value compared to previous machining processes. Thus, with the monitoring of this process, failures that would cause the parts to be discarded can be detected. One of the most preeminent non-intrusive methods of machining-process monitoring is the digital processing of in situ acquired acoustic emission (AE) signals. In recent published papers, a low-cost piezoelectric transducer has shown great results as an alternative to traditional AE sensors when applied in the monitoring of other machining processes such as grinding and dressing. Among the methods of evaluating a sensor’s response, the pencil lead break (PLB) method has shown to be effective when applied to different workpieces and low-cost transducers. The present work aims to evaluate the submerged influence on the low-cost piezoelectric transducer response by means of the PLB method for EEM monitoring. The results obtained show that there is great influence on the signal obtained when the piezoelectric transducer is in contact with the liquid interface. The results also show that the influence is more preeminent on certain frequency values.
Keywords: elastic emission machining; low-cost transducer; pencil lead break; process monitoring; signal processing